EFFECTIVENESS OF RED BETEL LEAF (PIPER CROCATUM) IN REDUCING SYMPTOMS OF FLUOR ALBUS IN WOMEN OF REPRODUCTIVE AGE - Mulyanti, Sri; Karo, Marni Br; M, Riyen Sari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Fluor albus is the presence of Trichomonas vaginalis and Candida albicans bacterial infections. Fluor albus itself is an excessive discharge from the vagina that is not menstrual blood. Red betel leaf is one of the potential medicinal plants that is empirically known to have properties to cure various types of diseases, including fluor albus. This research method employs a quantitative design, specifically the randomized pretest post-test control group design. The subjects selected in this study were women of childbearing age in Islamic boarding schools. The number of samples was 40 people. The data analysis used was univariate and bivariate using the sample t-test. Based on the results of statistical analysis using the t-test, a p-value of 0.000 0.05 was obtained. The result shows that Ho is rejected and Ha is accepted. So it can be concluded that there is an effect of boiled red betel leaf water (piper crocatum) on reducing fluor albus symptoms in women of childbearing age.